2023
DOI: 10.1111/echo.15526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ramus coronary artery on computed tomography derived fractional flow reserve (FFRCT) in no apparent coronary artery disease

Abstract: Background The ramus artery contributes to the development of turbulence, which may influence computed tomography (CT) derived fractional flow reserve (FFRCT) even without coronary artery disease (CAD). The relationship between ramus‐induced turbulence and FFRCT is unclear. Method and Results A total of 120 patients with <20% coronary stenosis assessed by both FFRCT and invasive coronary angiography were evaluated. The patients were divided into three groups: absent‐ramus (n = 72), small‐ramus that could not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This finding may be related to energy loss due to turbulence by the bifurcation from the left main trunk to LAD and LCX, or splitting into large branches such as diagonal branch, obtuse marginal branch, or posterior descending branch. Our previous study on the ramus artery demonstrated that the presence of a large ramus artery yields energy loss due to turbulence around the bifurcation angle, resulting in distal FFR CT decline in both LAD and LCX [ 23 , 24 ]. Turbulent eddies generated by the presence of large branches could contribute to energy loss, resulting in impact on FFR CT hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be related to energy loss due to turbulence by the bifurcation from the left main trunk to LAD and LCX, or splitting into large branches such as diagonal branch, obtuse marginal branch, or posterior descending branch. Our previous study on the ramus artery demonstrated that the presence of a large ramus artery yields energy loss due to turbulence around the bifurcation angle, resulting in distal FFR CT decline in both LAD and LCX [ 23 , 24 ]. Turbulent eddies generated by the presence of large branches could contribute to energy loss, resulting in impact on FFR CT hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] FFR CT (HeartFlow Inc., Redwood City, California, USA) was calculated based on a threedimensional anatomical model synthesized from CCTA data. [3][4][5][6][7][8] The vessel lengths of the proximal portion, stenotic lesion, and distal portion were 11 mm, 19 mm, and 96 mm, respectively (Figures 1A-B). The proximal and distal portions contained mild IAP, whereas the stenotic lesion was characterized by abundant IAP and CP (Figures 1C-J and 2), particularly in the middle part of the stenotic lesion surrounded by CP (Figure 1F).…”
Section: Case Reportmentioning
confidence: 99%